PARTICIPATION OF THE ARMED FORCES IN THE PROTECTION OF THE ENVIRONMENT IN LA PAMPA REGION MADRE DE DIOS, 2019-2020 - Ugaz Bartolo, Orlando Melvin (2021)
The objective of this research is to evaluate theparticipation of the Peruvian Armed Forces in theenvironmental protection in the area called LaPampa in the Madre de Dios region, during the period 2019-2020. The methodology is quantitative, of the applied type, themethod is hypothetical-deductive, correlational in scope,non-experimental-cross-sectional design. The population ofstudy is made up of officers of the Army of thePeru, Navy and Air Force, who worked inMadre de Dios region during the mentioned period.The study concludes that the participation of the Armed ForcesArmed Forces contributes directly and significantly toprotection of the environment in the area calledLa Pampa, a region that has natural resources veryimportant for the development of the national economy,as well as a vast territory that belongs to the Amazon,which requires a greater presence of the State in the formeffective, which occurs through the Armed Forces,responsible for protecting natural resources and promotingits sustainable development, among other aspects.